Tinjauan Hukum terhadap Ancaman Penyebarluasan Data oleh Anak Dibawah Umur (Study Putusan Nomor:4/Pid.Sus-Anak/2022/Pn Trt, Putusan Nomor:5/Pid.Sus-Anak/2022/Pn Trt dan Putusan Nomor:7/Pid.Sus-Anak/2022/Pn Trt) - Aritonang, Zico Ricardo; Hutasoit, Amsal Laurenzio G.B; Naibaho, Tito Martin; Demitri, Adrian Raja (UNES Law Review, 2024)
In an increasingly advanced digital era, minors are increasingly exposed to various technologies and access to the internet. This brings potential consequences in the form of uncontrolled data dissemination. Threats to data security and privacy are becoming increasingly pressing issues in this context. This research aims to review and analyze legal liability for personal data leakage and privacy. The research method used is a literature review that investigates the literature related to data security issues, privacy, and children's behavior in the use of technology. The findings of this study show that minors tend to be unaware of the implications of their actions on data security and privacy. They often do not understand the risks associated with sharing their personal information widely. The main threats identified include: threats of violence, coercion, perpetrating a series of lies and other physical dangers. The research also highlights factors that contribute to data sharing by minors, including lack of supervision from parents or caregivers, children's ignorance about data privacy and security, and high exposure to inappropriate online content. Indonesia has regulations as a legal basis in protecting children in the digital world, including Law No. 35 of 2014 concerning amendments to Law No. 23 of 2002 concerning Child Protection, Minister of Communication and Information Regulation No. 20 of 2016 concerning Personal Data Protection, and Government Regulation No. 43 of 2017 concerning the Implementation of Rostitution for children who are victims of criminal acts.